Nutrition and the governance of agri-food systems in South Asia: A systematic review. (January 2019) - Gillespie, Stuart; van den Bold, Mara; Hodge, Judith
Highlights: Despite improvement, political commitment is still tilted towards food security. Leaders must work across sectors to build alliances to address malnutrition. Nutrition governance requires a focus on processes, as well as structures. Horizontal and vertical coherence are both essential for progress in nutrition. Timely, actionable nutrition-relevant data are needed to improve accountability. Abstract: Malnutrition is a multicausal challenge that requires multisectoral responses to make comprehensive and sustainable progress, over the long term. How is agriculture and the wider agri-food system positioned within the constellation of factors and processes that determine nutrition outcomes in different contexts and countries? What is known about the role of enabling environments and the governance of agri-food systems in driving nutrition outcomes, for better or worse? In this paper we will highlight the findings of a systematic review that focuses on this question, drawing on work from the South Asian region including research undertaken by LANSA. We conclude with a discussion of the major implications and recommendations for future policy and practice.